Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

y= -2x - 3
y= 7x + 6 solve by elimination


Sagot :

Answer:

x = y = - 1

Step-by-step explanation:

y = - 2x - 3

y = 7x + 6 -----> equation 1.

So,

7x + 6 = - 2x - 3

7x + 2x = - 3 - 6

9x = - 9

Divide 9 on both sides,

9x / 9 = - 9 / 9

x = - 1

Substitute x = - 1 in equation 1,

y = 7x + 6

  = 7 ( - 1 ) + 6

  = - 7 + 6

  = 6 - 7

y = - 1

Therefore,

x = y = - 1

Step-by-step explanation:

please mark me as brainlest

View image bdilsai06